An Analytical System Design for Forensic Fingerprint Examination - Bilgehan Arslan; Seref Sagiroglu (IEEE Access)
Contactless visualization of latent fingerprints has gained considerable attention for crime scene investigations as it can offer an option to collect traces using non-invasive and non-destructive treatment. Considering the complex structure of fingerprint development methods and the tedious process steps performed in these methods, new approaches to acquire, store, transfer, and analyze latent fingerprints practically without requiring any deep knowledge and expertise are needed. This paper introduces a novel contactless latent fingerprint development method that uses a camera embedded in a mobile device and the apparatus used to increase the latent fingerprint’s visibility. The enhancement approach is presented to make the fingerprint collected with the designed apparatus usable and valid. As a result, an alternative system design for latent fingerprint development and enhancement is described in detail. Two state-of-the-art fingerprint matchers are used to measure the verification performance of the acquired latent fingerprint. It has been seen that latent fingerprints can be developed with contactless methods using optical treatments alone from reflective and non-porous surfaces. Furthermore, the stages of detecting, developing, and acquiring latent fingerprints from reflective and non-porous surfaces are carried out using the suggested development method without the requirement for forensic professionals. The proposed enhancement approach allows for the direct use of the enhanced fingerprint in the biometric identification/ verification system by extracting distinctive properties from the latent fingerprint.